2014
DOI: 10.1038/bjc.2014.128
|View full text |Cite
|
Sign up to set email alerts
|

Aza-deoxycytidine induces apoptosis or differentiation via DNMT3B and targets embryonal carcinoma cells but not their differentiated derivatives

Abstract: Background:Teratocarcinoma is a malignant male germ cell tumour, which contains stem cells and differentiated cancer tissues. DNMT3B has been shown to be highly expressed in human teratocarcinoma stem cells, and to mediate cytotoxicity of Aza-deoxycytidine (Aza-dC) in a pluripotent stem cell line NTERA2.Methods:We have established DNMT3B or POU5F1 (hereafter referred to as OCT4) knockdown in teratocarcinoma stem cells N2102Ep and TERA1 and in the pluripotent NTERA2 by a doxycycline-inducible system, and tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…Interestingly, many reactivated genes are also tumor suppressor genes [48] . Several reports have demonstrated that depletion of DNMT1, DNMT3A or DNMT3B can counteract the cytotoxic and apoptotic effect of Aza-dC on treated cancer cells, confirming the essential role of DNMTs in mediating the Aza-dC response [47,[50][51][52] . In contrast to with Aza when used at the same concentration, which might be associated with an increase in iron uptake and heme biosynthesis [55] .…”
Section: Inhibition Of Dnmts By Aza-dcmentioning
confidence: 75%
See 1 more Smart Citation
“…Interestingly, many reactivated genes are also tumor suppressor genes [48] . Several reports have demonstrated that depletion of DNMT1, DNMT3A or DNMT3B can counteract the cytotoxic and apoptotic effect of Aza-dC on treated cancer cells, confirming the essential role of DNMTs in mediating the Aza-dC response [47,[50][51][52] . In contrast to with Aza when used at the same concentration, which might be associated with an increase in iron uptake and heme biosynthesis [55] .…”
Section: Inhibition Of Dnmts By Aza-dcmentioning
confidence: 75%
“…Subsequently, DNMT3B has been reported to play a significant role in activation of DNA damage response and expression of p53 target genes induced by Aza-dC in human pluripotent EC cell line NTERA2 [100] . Albeit having the cytotoxic effect on the cancer stem cells, Aza-dC fails to induce apoptosis of differentiated cells derived from human nullipotent EC cells, which can be isolated from teratocarcinoma more frequently than their pluripotent counterparts [52] . Although human nullipotent EC cells undergo apoptosis induced by AzadC, they do not differentiate.…”
Section: Testicular Germ Cell Tumorsmentioning
confidence: 99%
“…Mechanistically, the anti-neoplastic effect of HMAs is thought to mainly result from a global DNA demethylation allowing for re-expression of silenced genes, including tumor suppressor genes and testis cancer antigens (Steele et al, 2009;Pleyer & Greil, 2015). The activity of DAC and GDAC has been closely linked to an overexpression of DNMT3B and an intact p53dependent apoptosis induction (Beyrouthy et al, 2009;Biswal et al, 2012;Wongtrakoongate et al, 2014;Albany et al, 2017). Moreover, pre-treatment with DAC or GDAC resulted in a remarkable re-sensitization towards cisplatin in mouse models using cisplatin-resistant GCT or ovarian cancer cells lines (Steele et al, 2009;Albany et al, 2017).…”
Section: Hmas Plus Chemotherapymentioning
confidence: 99%
“…DAC induces differentiation, apoptosis, and senescence in leukemic cells in vitro 32 – 34 and also other cancer cell types. 35 – 37 These results show the potential of DAC in treating malignant disease, and thus we have examined the effects of DAC on the differentiation of BCSCs in vitro.…”
Section: Introductionmentioning
confidence: 98%